2011
DOI: 10.1002/clc.20926
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Contemporary Percutaneous Coronary Intervention in the Elderly and the Very Elderly: Insights From the Blue Cross Blue Shield of Michigan Cardiovascular Consortium

Abstract: Background: There is a paucity of data on the outcome of contemporary percutaneous coronary intervention (PCI) in the elderly. Accordingly, we assessed the impact of age on outcome of a large cohort of patients undergoing PCI in a regional collaborative registry. Hypothesis: Increasing age is associated with a higher incidence of procedural-related complications. Results: Of the cohort, 64.64% were <70 years of age, 23.83% were 70 to 79 years, 7.85% were 80 to 84 years, 3.09% were 85 to 89 years, and 0.58% wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
2
17
1
Order By: Relevance
“…It is a common view that the elderly STEMI patients, especially the ≥75 year population, have more complex coronary artery disease and high complications risks [4][5][6][7][8]. And our research had similar findings that the ≥75 year STEMI group had more serious clinical characteristics in comparison with the 60-75 year group.…”
supporting
confidence: 76%
“…It is a common view that the elderly STEMI patients, especially the ≥75 year population, have more complex coronary artery disease and high complications risks [4][5][6][7][8]. And our research had similar findings that the ≥75 year STEMI group had more serious clinical characteristics in comparison with the 60-75 year group.…”
supporting
confidence: 76%
“…These complication rates were in line with the other published studies. Thomas et al reported increased risk of adverse events in elderly patients undergoing PCI with an approximate 4% in-hospital mortality, 1% stroke and 4% vascular complications [17]. The STEMI group has higher in-hospital mortality rate (10%) in our series, which is in concordance with existing data [17,18].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, subgroup analysis of the GRACE registry suggests that an octogenarian population following a presentation with highrisk non-ST-elevation acute coronary syndrome has significantly less mortality when PCI is performed [11]. The adverse outcomes such as all-cause in-hospital mortality, contrast-induced nephropathy, transfusion, stroke/transient ischemic attack and vascular complications are higher with increasing age [17]. (7) Total MACE, n (%) a 82 (54) MACE: major adverse cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it indicated that CIN in elderly patients may be associated with prolonged renal dysfunction and poor prognosis. According to a recent study 14) in a large cohort of patients undergoing percutaneous coronary intervention (PCI), the overall in-hospital mortality rate was 1.09%, and it increased from 0.67% to 5.44%, compared with those in patients < 70 years and > 90 years. Furthermore, it was also pointed out that increasing age was associated with an increase in in-hospital mortality rates and CIN incidence.…”
Section: )mentioning
confidence: 99%